2015
DOI: 10.1051/bioconf/20150501020
|View full text |Cite
|
Sign up to set email alerts
|

Cluster thinning in cv. Verdejo rainfed grown: Physiologic, agronomic and qualitative effects, in the D.O. Rueda (Spain)

Abstract: Abstract. The control of grape yield can be a critical aspect for grape quality of white varieties, moreover in the conditions of high water limitation that occurs in most Spanish growing regions. In the case of Verdejo variety, it is necessary to know its response to the reduction of the number of clusters per vine in order to regulate the production and improve the grape quality. During the period 2012-2014, the application of cluster thinning has been studied, by means of a treatment (A) of removing 27% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Naor et al, 2002;Sun et al, 2012 andRescic et al, 2015 noted that the reduction of yield weight resulted from cluster thinning led to a significant increase of cluster weight. Cluster thinning reduced yield weight by about 20-40% depending on thinning severity and/or the cultivar, (Palliotti and Cartechini, 1998;Guidoni et al, 2002;Elsalhy et al, 2010;Kok, 2011;Gil et al, 2013 andVicente andYuste, 2015). The later accordant with the findings of current study which found that the severe cluster thinning by removing 30% of the clusters reduced yield by 37.2 and 39.2% in the two season of study.…”
Section: Discussionsupporting
confidence: 86%
“…Naor et al, 2002;Sun et al, 2012 andRescic et al, 2015 noted that the reduction of yield weight resulted from cluster thinning led to a significant increase of cluster weight. Cluster thinning reduced yield weight by about 20-40% depending on thinning severity and/or the cultivar, (Palliotti and Cartechini, 1998;Guidoni et al, 2002;Elsalhy et al, 2010;Kok, 2011;Gil et al, 2013 andVicente andYuste, 2015). The later accordant with the findings of current study which found that the severe cluster thinning by removing 30% of the clusters reduced yield by 37.2 and 39.2% in the two season of study.…”
Section: Discussionsupporting
confidence: 86%
“…On the other hand, clusters thinning is a common management technique executed by grape growers to control the production amount to be within the limits of the natural load and improve clusters quality (Fawzi & Abd El-Moniem 2003, Nuzzo, 2004. In addition, thinning of clusters or berries determines the clusters' size, directly promoting their ripening, sugar contents, and anthocyanins (El-Salhy et al, 2010, Vicente & Yuste, 2015. Cluster thinning also affects the availability of stored food material required to grow developing cluster after the fruit thinning.…”
Section: Introductionmentioning
confidence: 99%
“…Hand thinning plays an important role in some grape varieties, since its control crop and improves its quality and hastens the ripening (Dhillon et al, 1992;Fitzgerold and Patterson, 1994;Keller et al, 2005;Selim, 2007;Diago et al, 2010 andEl-Salhy et al, 2010). Mechanical clusters thinning (Petrie and Clingeleffer, 2006;Tardaguila et al, 2008 andVicente andYuste, 2015) and chemical thinning by using specific chemical agents, i.e., ethephon, gibberellic acid and naphthalene acetic acid (Kokl and Ball, 2017). However, potential risk might be occurred due to the use of the above mentioned chemicals.…”
Section: Introductionmentioning
confidence: 99%